2015
DOI: 10.1007/s11356-015-5007-4
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the dogma: PCB-derived semiquinone free radicals do not form covalent adducts with DNA, GSH, and amino acids

Abstract: Covalent bond formations of free radical metabolites with biomolecules like DNA and proteins are thought to constitute a major mechanism of toxicity and carcinogenesis. Glutathione (GSH) is generally accepted as a radical scavenger protecting the cell. In the present study, we investigated a semiquinone radical (SQ•-) metabolite of the semivolatile 4-chlorobiphenyl, using electron paramagnetic resonance spectroscopy, and oxygen consumption. Proton nuclear magnetic resonance (1H NMR) and liquid chromatography–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The derivatives contained one or two methylthioether groups indicating PCB3-pQ formed covalent bonds with one or two GSH through sulfhydryl groups (shown in Figure 2-1). The same results were also shown in previous research for incubation of GSH with PCB quinoid metabolites (Song et al 2009, Wangpradit et al 2015. Derivatives with two methylthiol groups were also found in microsomal incubation samples with HRP (Figure 2-3).…”
Section: Amount Of Pcb3 (Nmol) Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The derivatives contained one or two methylthioether groups indicating PCB3-pQ formed covalent bonds with one or two GSH through sulfhydryl groups (shown in Figure 2-1). The same results were also shown in previous research for incubation of GSH with PCB quinoid metabolites (Song et al 2009, Wangpradit et al 2015. Derivatives with two methylthiol groups were also found in microsomal incubation samples with HRP (Figure 2-3).…”
Section: Amount Of Pcb3 (Nmol) Discussionsupporting
confidence: 89%
“…Protein or DNA Adducts from PCB Metabolites These arene oxide and quinoid metabolites of PCBs were considered as highly reactive (Ludewig et al 2008). Though semiquinone radicals in the quinone/semiquinone/hydroquinone triad were considered reactive to form covalent binding with DNA or proteins, recent research found the PCB-derived semiquinone free radicals do not form covalent adducts with DNA, GSH, and amino acids (Wangpradit et al 2015). The reactive metabolites, the arene oxide and quinoid metabolites of PCBs, can react towards nucleophiles on DNAs and proteins.…”
Section: Protein Adducts By Reactive Electrophilesmentioning
confidence: 99%
“…Interestingly, the data shown in Figure 8 has the same trend as that of interaction of species (generated electrochemically) with the four nucleobases. It was reported earlier DNA and oligonucleotides tend to stabilize semiquinone radical anions through delocalization of electrons in a π-stacking framework, that result in a radical intercalated situation rather than forming covalent bonds [ 43 ]. This was further supported by some semi-empirical calculations showing there is a gain in energy by ~ 9.8 kcal mol −1 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…With increase in percentage of water, two reduction peaks approach each other and a single step two electron reduction occurs [ 56 , 57 ]. Quinone-dianion and free quinone upon comproportionation form semiquinone radical anion that undergoes disproportionation as well [ 28 , 33 , 41 , 42 , 43 , 58 , 59 , 60 ]. This was again verified as a part of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation